Peran Leadership Dalam Meningkatkan Kedisiplinan dan Performa Karyawan Di PT Duta Intidiya, Tbk (Watsons Indonesia) - Jordan, Michael; Istiqamah, Nuraini Kemalasari (Universitas Negeri Medan, 2025)
Leadership is the ability to stimulate, mobilize, direct, coordinate and influence others in doing somethingto achieve organizational goals. The success or failure of efforts to achieve organizational goals is determined by thequality of leadership. The problem in this study is how the role of leadership in improving employee discipline andperformance. This study aims to determine the role of leadership in improving employee discipline and performanceat PT Duta Intidiya Tbk (Watsons Indonesia). The data collection method used in the study is descriptive analysis.The results of this study show that the role of the leadership of PT Duta Intidaya Tbk (Watsons Indonesia) in improvingemployee performance is quite good in improving employee performance, which can be seen in terms of sales thathave increased in achievements, where sales results have increased. From the role of the leader, he has also provideddirections that establish good cooperation among employees by providing support, guidance, and input to employeesto be able to improve their performance. The leadership always directly monitors the problems that occur and conveyssome information about the company to external parties of the company for a work plan and policy in the smoothperformance of the company.